Social media engagement in the maritime industry during the pandemic - Koh, Le Yi (2023)
The maritime sectors are suffering severe disruptions as a result of COVID-19. Maritime companies have turned to social media to interact with partners and clear up confusion. However, not every social media post receives the same engagement levels especially during a pandemic. For a more holistic analysis of social media engagement during a pandemic, the Protection Motivation Theory and classical theories such as user gratification and media richness theories were included. The research uses hierarchical regression analysis on information gathered from Facebook posts about COVID-19 made by eighteen different companies from four distinct maritime sectors. It was found that the rate of stakeholder engagement is highly influenced by informational, relational, and entertaining content as well as content that fosters self-efficacy, severity, and vulnerability. Additionally, the stakeholder engagement rate is greatly influenced by posts with greater vividness and fluency, which are characterized by providing external links. This is the first study to look into why stakeholders interact with posts linked to COVID-19 on social media. The findings will help maritime organisations use social media as a management and communication instrument.